2015
DOI: 10.1051/0004-6361/201425341
|View full text |Cite
|
Sign up to set email alerts
|

Reflection nebulae in the Galactic center: soft X-ray imaging polarimetry

Abstract: Context. The origin of irradiation and fluorescence of the 6.4 keV bright giant molecular clouds surrounding Sgr A * , the central supermassive black hole of our Galaxy, remains enigmatic despite numerous attempts to decipher it with spectroscopic and timing analyses. Aims. Testing the theory of a past active period of Sgr A * requires opening a new observational window: X-ray polarimetry. In this paper, we aim to show how modern imaging polarimeters could revolutionize our understanding of the Galactic center… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(78 citation statements)
references
References 44 publications
(63 reference statements)
5
72
0
1
Order By: Relevance
“…Below we use the effective area and the modulation factor from Soffitta et al (2013). A similar question has already been addressed in Marin et al (2015) based on the assumed positions of several clouds. In our simulations the uncertainties in the choice of the 3D gas 6 Note, that the degree of polarization depends on the cosine of the scattering angle, i.e.…”
Section: Feasibilitymentioning
confidence: 74%
See 1 more Smart Citation
“…Below we use the effective area and the modulation factor from Soffitta et al (2013). A similar question has already been addressed in Marin et al (2015) based on the assumed positions of several clouds. In our simulations the uncertainties in the choice of the 3D gas 6 Note, that the degree of polarization depends on the cosine of the scattering angle, i.e.…”
Section: Feasibilitymentioning
confidence: 74%
“…There were many studies that consider the reflection scenarios in the GC region (e.g., Murakami et al 2000;Molaro, Khatri, & Sunyaev 2016;Marin et al 2015). Here we return to this problem to emphasize the power of long-term monitoring of the reflected emission.…”
Section: Introductionmentioning
confidence: 99%
“…Scattered flux from Sgr B2 in hard X-rays has also been detected using Integral (Revnivtsev et al 2004). Similarly, other GMCs in the CMZ (Murakami et al 2001;Marin et al 2015) have since been shown to act as XRNe. An alternative scenario to the reflection of past Sgr A * flares, which explains the 6.4 keV emission in Sgr B2 as the result of the interaction of low-energy cosmic ray electrons with matter in the GMCs, has also been proposed (Valinia et al 2000;Yusef-Zadeh et al 2002;Yusef-Zadeh 2013;Dogiel et al 2009).…”
Section: Introductionmentioning
confidence: 90%
“…In the latter case, the very low X-ray fluxes, coupled with relatively low or inexistent polarization from galaxy clusters, naturally explains why the publication rate in this field is the lowest. Until the advent of extra-sensitive X-ray polarimeters, it is not mandatory to explore in greater detail the expected polarization of quiescent galaxies (save the Milky Way, where important and feasible observations await us [22][23][24]). Several subcategories are highlighted: the black solid line represents general publications on X-ray polarimetry (reviews, historical notes); violet stands for publications concerning theory, instrumentation, and satellites, red for papers on solar, stellar, and exoplanet science; orange for papers on objects dominated by strong gravity effects (e.g., black holes); yellow for objects dominated by strong magnetic fields (e.g., neutron stars); the green solid line stands for papers related to galaxies (e.g., galaxy clusters or the Milky Way).…”
Section: Publication Per Fieldmentioning
confidence: 99%